2008
DOI: 10.1590/s0100-29452008000100019
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos biológicos de Dione juno juno (Cramer) (Lepidoptera: Nymphalidae) em genótipos de maracujazeiro

Abstract: Avaliou-se o efeito de genótipos de maracujazeiro no desenvolvimento de Dione juno juno (Cramer) (Lepidoptera: Nymphalidae). O experimento foi conduzido em laboratório, sob condições ambientais controladas (temperatura de 26 ± 1ºC, U. R. de 60 ± 10% e fotofase de 14 horas). Lagartas recém-eclodidas foram alimentadas com folhas de genótipos de maracujazeiro: Passiflora edulis Sims., P. alata Dryand., P. serrato-digitata L., P. edulis f. flavicarpa Deg. ('Sul Brasil'), P. edulis f. flavicarpa, P. edulis f. flavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Um caso é o da eficiência do uso antibacteriano de extratos de folhas e frutos (Mohanasundari et al, 2007;Bhosale & Sutar, 2015), sendo que os principais metabólitos secundários encontrados em folhas, ramos, frutos e sementes são alcaloides, flavonoides, compostos glicosídeos cardíacos, antraquinonas e saponinas (Bhosale & Sutar, 2015). Tricomas presentes principalmente nas flores, frutos, brácteas e estípulas, secretam resina que apresenta defesa contra lagartas de Dione juno juno (Boiça Júnior et al, 2008).…”
Section: Introductionunclassified
“…Um caso é o da eficiência do uso antibacteriano de extratos de folhas e frutos (Mohanasundari et al, 2007;Bhosale & Sutar, 2015), sendo que os principais metabólitos secundários encontrados em folhas, ramos, frutos e sementes são alcaloides, flavonoides, compostos glicosídeos cardíacos, antraquinonas e saponinas (Bhosale & Sutar, 2015). Tricomas presentes principalmente nas flores, frutos, brácteas e estípulas, secretam resina que apresenta defesa contra lagartas de Dione juno juno (Boiça Júnior et al, 2008).…”
Section: Introductionunclassified
“…Five saponins were described from P. alata leaves (Reginatto et al, ), the most abundant being quadranguloside, also found in P. quadrangularis (Reginatto et al, ). D. juno larvae had 100% mortality when fed with P. alata leaves (Boiça Júnior, Angelini & De Oliveira, ) and larvae of Heliconius erato and Heliconius charithonia did not consume P. quadrangularis leaves in feeding assays (Smiley, ). Consequently, quadranguloside could be effective against some heliconiine herbivores.…”
Section: Chemical Defences Of Passsifloramentioning
confidence: 99%
“…Insect pests, including Dione juno juno Cramer, 1779 (Lepidoptera: Nymphalidae), feed on leaves and branches, reducing the production of the yellow passion fruit Passiflora edulis Sims (Boiça Júnior et al, 2008). This pest is mainly controlled with chemical insecticides that can contaminate food, water, and soil, besides reducing populations of natural enemies and facilitating the emergence of resistant insects (Amatuzzi et al, 2018;Costa et al, 2020).…”
mentioning
confidence: 99%